Hematological and Biochemical Parameters along with IgG Antibody against SARS-CoV-2 in Patients visiting a referral laboratory for recovery check up after COVID-19 infection in Nepal - Pant, Vivek; Gautam, Keyoor; Pradhan, Santosh; Pyakurel, Devish; Shrestha, Abha (Journal of Nepal Health Research Council, 2021)
Background: The laboratory abnormalities for hospitalized patients with the SARS-CoV-2 have been described in various studies. Limited data are available for the recovered patients. This study aimed to evaluate various laboratory findings in the recovered SARS-CoV-2 patients.Methods: In this cross sectional study, the laboratory findings of various hematological and biochemical parameters along with antibody against SARS-CoV-2 of 150 patients who visited Samyak Diagnostic Pvt. Ltd for recovery check up after SARS-CoV-2 were studied from October 2020 to March 2021.Results: Out of total 150 participants, 84% of SARS-CoV-2 recovered patients, who had mild or moderate illness, reported persistence of milder symptoms. Persistence of high serum inflammatory markers such as CRP, Ferritin and LDH along with abnormal cell count and morphology of leukocyte lineage was present in 45.4% of these patients. Similarly, 98.7 % had SARS-CoV-2 IgG antibody after 37 median days of recovery. Conclusions: Various laboratory abnormalities may persist after SARS-CoV-2 recovery in addition to the presence of SARS-CoV-2 IgG antibody. Follow up study is needed to determine the period up to which these abnormalities are present and the protection from antibody is conferred.Keywords: SARS-CoV-2; SARS-CoV-2 recovery; SARS-CoV-2 IgG antibody